Analisis Metode Job Order Costing Untuk Menentukan Harga Jual Ecoprint Dalam Perspektif Bisnis Syariah - Ruly Priantilianingtiasari; Zaki Bahrun Ni'am (Univiversitas Dr. Djar Wattiheluw, 2024)
The uniqueness of ecoprint fabric in batik, serving as an iconic symbol of the Indonesian nation. The intricate and distinctive production process leads to varying selling prices. However, a challenge lies in the inaccurate estimation of production costs and product selling prices. This prompts the need for studies on determining product prices in line with Sharia principles from a Sharia business perspective. The research problem formulation includes determining production costs using the job order costing method for Jati Aji ecoprint batik products, selecting a method for determining ecoprint batik selling prices, and establishing selling prices from a Sharia business perspective. The research employs a qualitative method, utilizing field observation, interviews, and literature study for data collection. The results reveal that Jati Aji batik hasn't implemented the job order costing method, prompting the researcher to provide calculation recommendations. Pricing methods involve demand-based, cost-based, profit-based, and competition-based pricing. Determining the selling price of ecoprint products aligns with the thoughts of Muslim leaders, emphasizing fair and reasonable prices based on demand and supply.